ANALYSIS OF FACTORS THAT INFLUENCE THE FINANCIAL SATISFACTION OF WORKERS IN JAKARTA - Natsir, Khairina; Arifin, Agus Zainul; Devy, Devy (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to examine the influence of Financial Knowledge and Income on Financial Satisfaction where Financial Behavior acts as an intervening variable. This research was conducted on the workers who are still actively working in Jakarta. The sampling method is purposive sampling. The sample in this study amounted to 400 respondents who were obtained through distributing questionnaires to workers directly, and online via Google questionnaire. Data is analyzed using the structural equation modeling technique. The tests carried out include testing the outer model and inner model. The research results show that Financial Knowledge has a significant influence on Financial Behavior. Meanwhile, income does not have a significant influence on financial behavior. Furthermore, Financial Behavior, Financial Knowledge, and Income have a significant influence on Financial Satisfaction. Financial Behavior mediates the relationship between Financial Knowledge on Financial Satisfaction, but Financial Behavior does not mediate the relationship between Income and Financial Satisfaction. The results of this research are following with the predictions of Planned Behavior Theory, Behavioral Finance Theory, and telic theory.